(untitled) (Journal of Information Technologies in Education (ITE), 2012)
This article discusses issues related to the preparation of business analysts in higher education in Russia. Described the subject area of business analysis, described the place and role of the business analyst in the organization. The recommendations on the formation of a set of competencies business intelligence, as well as the integration of disciplines in the curriculum.